2017
DOI: 10.1016/j.jvs.2017.04.072
|View full text |Cite
|
Sign up to set email alerts
|

Increasing use of endovascular therapy in pediatric arterial trauma

Abstract: The use of endovascular therapy in pediatric vascular arterial trauma has significantly increased, especially among severely injured blunt trauma patients. Despite this successful integration into care, there was no in-hospital survival advantage conferred by endovascular therapy compared with traditional open therapy. Approximately 10% of children with arterial injuries died during initial trauma assessment before therapy could be offered. Glasgow Coma Scale score ≤8, ISS ≥16, positive result of ethanol or dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…At present, trauma to the visceral aorta (Case 5) is an absolute contradiction to EVT Angioembolisation for bleeding is a standard procedure in paediatric arterial trauma. 3 In contrast, thromboaspiration is rare but has been successfully performed in the pulmonary artery, iliac artery, central veins and femoral arteries 12 13 for traumatic and non-traumatic aetiology. There is limited literature on thromboaspiration of visceral arteries which makes our case of renal artery thrombectomy unique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, trauma to the visceral aorta (Case 5) is an absolute contradiction to EVT Angioembolisation for bleeding is a standard procedure in paediatric arterial trauma. 3 In contrast, thromboaspiration is rare but has been successfully performed in the pulmonary artery, iliac artery, central veins and femoral arteries 12 13 for traumatic and non-traumatic aetiology. There is limited literature on thromboaspiration of visceral arteries which makes our case of renal artery thrombectomy unique.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic aortic injury (TAI) can be catastrophic when of the severe grade, and 73% of patients die en-route to the hospital. 3 Patients with TAI also have severe concurrent injuries of the cranium, torso and the extremities. 4 Both the low incidence and the presence of multi-system trauma make recognition and management of this condition very challenging.…”
mentioning
confidence: 99%
“…The use of endovascular therapy has increased in pediatric patients since 2007. Another review of the NTDB including 2007-2014 reported increase in this technique from 7% to 12% [7].…”
Section: Epidemiologymentioning
confidence: 99%
“…The incorporation of endovascular techniques such as temporary balloon control and stent grafting to traditional open surgery has not only enhanced management options for bleeding trauma patients, but has also positively impacted morbidity and mortality after these injuries. [7][8][9][10][11][12] Studies supporting the use of endovascular therapy continue to emerge in the literature as resources for endovascular therapy become more readily available at trauma centers and endovascular providers continue to get acquainted with this new technology. [7][8][9][10][11][12][13][14][15][16][17] The purpose of this study was to explore patterns in modern epidemiology and mortality after IVC and aortic injuries in the United States.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12] Studies supporting the use of endovascular therapy continue to emerge in the literature as resources for endovascular therapy become more readily available at trauma centers and endovascular providers continue to get acquainted with this new technology. [7][8][9][10][11][12][13][14][15][16][17] The purpose of this study was to explore patterns in modern epidemiology and mortality after IVC and aortic injuries in the United States. We hypothesized that these injuries would remain highly lethal in the contemporary civilian setting, despite the ongoing endovascular revolution and other advancements in trauma care.…”
mentioning
confidence: 99%